Hemophilia therapy: the future has begun - Mannucci, Pier Mannuccio (Haematologica (Roma), 2020)
The success story of hemophilia care first began in the 1970s, when the availability of plasma-derived concentrates of coagulation factor VIII (FVIII) and factor IX (FIX) provided efficacious treatment of bleeding in patients with hemophilia A and B. This positive scenario was consolidated in terms of greater safety and availability in the 1990s, when the first recombinant coagulation factors were produced. This meant that, instead of only treating episodic bleeding events, prophylaxis regimens could be implemented as a preventive measure. Following the demonstration of its superiority in the frame of two randomized clinical trials, prophylaxis became evidence-based standard of care. In high-income countries, these achievements have led to a patients' life expectancy being extended to close to that of the general male population. Alongside this, the last decade has witnessed further spectacular therapeutic progress, such as the availability of coagulation factors with a longer plasma half-life that allow for wider intervals between treatment. Moreover, new therapeutic products based on new mechanisms other than the replacement of the deficient factor, have become available (emicizumab) or are at an advanced stage of development. This review celebrates the success story of hemophilia care, while also discussing current limitations, issues and as yet unmet needs. The prospects of cure by means of gene therapy are also outlined.